Homotopy theory of cyclic presheaves - Seteklev, Sigurd; Østvær, Paul Arne (MATHEMATICA SCANDINAVICA, 2010)
We generalize the homotopy theory of cyclic sets to cyclic presheaves on small Grothendieck sites. This is achieved by constructing pointwise and local model structures reminiscent of the homotopy theory of simplicial presheaves.